Correlation of Immunohistochemical Markers and BRAF Mutation Status with Histological Variants of Papillary Thyroid Carcinoma in the Korean Population - Min, Hye Sook; Lee, Chul; Jung, Kyeong Cheon (Journal of Korean medical science, 2013)
Several pathologic characteristics are associated with an adverse clinical outcome in papillary thyroid carcinoma (PTC), including the histological variant. This study aimed to investigate immunohistochemical expression and BRAF mutation status based on the histological variant and evaluated potential markers of aggressive behavior of PTC in Korean patients. In all, 407 PTC cases were classified to each histological variant, and the 94 representative cases were subjected to immunohistochemistry and BRAF mutation analysis. The classic type, follicular variant (FV) and tall cell variant (TCV) represented 76.9%, 14.2% and 6%, respectively. TCV showed a larger tumor size (P = 0.009), frequent extrathyroidal extension (P = 0.022) and cervical lymph node (LN) metastasis (P = 0.018). TCV and FV showed the reduced expression of galectin-3 (P = 0.003) and HBME1 (P = 0.114). Regardless of histology, PTEN loss and diffuse S100A4 expression were associated with LN metastasis (P = 0.007, P = 0.013). All TCVs harbored BRAF V600E mutation, and FV harbored less BRAF V600E mutation (P = 0.043). Immunohistochemical evaluation showed characteristic patterns in histological variants. PTEN and S100A4 expression are suggested as indicators of regional lymph node metastasis.